(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The flow and heat transfer properties of a Casson liquid past an exponential stretching sheet under the influence of transverse magnetic-field are investigated in this work. The numerical simulations were solved by using Keller Box method. The impact of various flow quantities such as the Casson fluid parameter, magnetic-field parameter, Prandtl number, and suction parameters on velocity and temperature fields are analysed through graphs. Moreover, the current method is compared with the existing methods, and the results are found to be similar.